New insights on the inscription on a painted pan-grave Bucranium, grave 3252 at Cemetery 3100/3200, Mostagedda (Middle Egypt) - Cooper, J; Barnard, H (Springer, 2017)
The so-called pan-graves occur in the archaeological record of the Egyptian Nile Valley during the Second Intermediate Period (13th–17th Dynasties, 1950–1550 BCE). Because of their uncharacteristic layout and contents they are usually interpreted as associated with a foreign group coming into the region from the south or southeast. Only a single text, comprising six Egyptian hieroglyphs painted on the skull of a bovid, can be connected with certainty to these graves and the people who constructed them. Since its excavation and analysis in the 1930s, this inscription has been interpreted as the personal name or title Ksk3nt, ‘master of the horn.’ Our new examination of the original materials questions this reading and suggests some new etymological possibilities. The text likely transcribes an ancient East African language such as Beja and is of insufficient length to be translated with certainty.